2016
DOI: 10.1016/j.msec.2015.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed Ti–Nb–Zr–Ta–Si–Fe biomedical beta titanium alloys with increased strength and enhanced biocompatibility

Abstract: Beta titanium alloys are promising materials for load-bearing orthopaedic implants due to their excellent corrosion resistance and biocompatibility, low elastic modulus and moderate strength. Metastable beta-Ti alloys can be hardened via precipitation of the alpha phase; however, this has an adverse effect on the elastic modulus. Small amounts of Fe (0-2 wt.%) and Si (0-1 wt.%) were added to Ti-35Nb-7Zr-6Ta (TNZT) biocompatible alloy to increase its strength in beta solution treated condition. Fe and Si additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(78 citation statements)
references
References 64 publications
5
71
0
2
Order By: Relevance
“…However, α + β Ti alloys generally have lower notched fatigue resistance and poorer wear characteristics compared to metastable beta Ti alloys [75]. Another consideration is the modulus of elasticity mismatch between α + β Ti alloys, which is approximately between 110 GPa and 115 GPa, and cortical bone, which is approximately 30 GPa [11,30]. The stiffer implant carries the load rather than the bone, which atrophies and loses density (osteopenia) due to lack of functional stimulation in a process known as stress shielding [77].…”
Section: Biomedical Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, α + β Ti alloys generally have lower notched fatigue resistance and poorer wear characteristics compared to metastable beta Ti alloys [75]. Another consideration is the modulus of elasticity mismatch between α + β Ti alloys, which is approximately between 110 GPa and 115 GPa, and cortical bone, which is approximately 30 GPa [11,30]. The stiffer implant carries the load rather than the bone, which atrophies and loses density (osteopenia) due to lack of functional stimulation in a process known as stress shielding [77].…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…More recently, several new experimental metastable beta Ti alloys have been developed including Ti-35Nb-7Zr-6Ta-(0-2)Fe-(0-1)Si (wt. %) [30], Ti-8Mo-(4-6)Nb-(2-5)Zr (wt. %) [31], Ti-33Nb-4Sn (wt.…”
Section: Biomedical Implantsmentioning
confidence: 99%
“…Considering the biocompatibility and the stability of β phase, β stabilizers such as Mo, Ta, Nb, Hf, Pd and Fe are usually selected as primary additive elements in the design of a β-type biomedical Ti alloy. Moreover, Zr can be used as a β stabilizer when used with combination of other β stabilizers such as Ta and Nb, and improve the performance of the Ti alloys202122232425. In this study, Ta, Zr and Hf were selected as the β stabilizers in order to achieve improved performance of the Ti alloys.…”
mentioning
confidence: 99%
“…In addition, our earlier study, also performed on β‐Ti alloys, showed that the adhesion and proliferation of human osteoblast‐like U‐2 OS cells and primary human osteoblasts on Ti–35Nb–7Zr–6Ta (TNZT) with various small additions of Fe and Si (particularly those with 0.5 wt % of Si+ 2 wt % of Fe) were higher than on the Ti‐6Al‐4 V alloy. At the same time, the number of U‐2 OS cells on Ti‐6Al‐4 V was significantly lower than in control tissue culture polystyrene wells (by about 25%), and the number of human osteoblasts on Ti‐6Al‐4 V was even ∼8.5 times lower than on polystyrene wells . The TNZT alloys also better promoted the production of collagen I, that is, an early marker of osteogenic differentiation, in primary human osteoblasts than the Ti‐6Al‐4 V alloy and standard cell culture polystyrene dishes .…”
Section: Discussionmentioning
confidence: 90%